Cord Blood Autobanks: Cryopreservation and Testing Methods - Babijchuk, L. A.; Kudokotseva, O. V.; Zubov, P. M.; Ryazantsev, V. V.; Zubova, O. L.; Gurina, T. M. (Problems of Cryobiology and Cryomedicine, 2008)
There was developed the technology of the cord blood nucleated cell cryopreservation which allowed to reduce DMSO concentration till 5% and provide the high recovery and structural and functional integrity of the mononuclear cell fraction in the preparation including the hemopoietic CD34+-stem cells.